2019
DOI: 10.1103/physrevmaterials.3.025001
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the electronic structure of OsO2 using soft and hard x-ray photoelectron spectroscopy in combination with density functional theory

Abstract: Theory and experiment are combined to gain an understanding of the electronic properties of OsO 2 , a poorly studied metallic oxide that crystallizes in the rutile structure. Hard and soft valence-band x-ray photoemission spectra of OsO 2 single crystals are in broad agreement with the results of density-functional-theory calculations, aside from a feature shifted to high binding energy of the conduction band. The energy shift corresponds to the conduction electron plasmon energy measured by reflection electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Such agreement between peak positions and intensities predicted by hybrid DFT with XPS is similar to previous reports in a variety of d -block materials in the absence of plasmon features. 59 61 In addition, we detect Cs, Zr, and Cl in the XPS survey scan (see Figure S10 and the SI for details), which is consistent with the expected presence of these elements for the Cs 2 ZrCl 6 NC thin film sample.…”
supporting
confidence: 82%
“…Such agreement between peak positions and intensities predicted by hybrid DFT with XPS is similar to previous reports in a variety of d -block materials in the absence of plasmon features. 59 61 In addition, we detect Cs, Zr, and Cl in the XPS survey scan (see Figure S10 and the SI for details), which is consistent with the expected presence of these elements for the Cs 2 ZrCl 6 NC thin film sample.…”
supporting
confidence: 82%
“…While there had been some debate on the origin of the major emission at 6.0 eV, Grovesnor et al used REELS to determine both surface and bulk plasmons as the primary origin of these emissions (though small shake-up features could not be discounted as contributing), and further observed a similar process within Co metal. 375 Similar insights are available to more complex systems, such as metal oxides 376,377 and semiconductors. 378 For example, REELS has been used in combination with XPS and theoretical calculations to probe OsO 2 where again, REELS was able to identify the presence and energy of a plasmon.…”
Section: Probing Surface Valence and Conduction Band Electronic Propertiesmentioning
confidence: 92%
“…This measurement contributed to the complete understanding of the electronic configuration through theoretical modelling of the density-of-states applied to the valence region of the photoelectron spectrum. 376…”
Section: Probing Surface Valence and Conduction Band Electronic Propertiesmentioning
confidence: 99%
“…To date, no theoretical study of satellites in tungsten has been reported. Such a treatment requires the use of many-body perturbation theory (MBPT), which has already shown promise for the determination of plasmon satellites in sodium [35], aluminium [35,36], germanium [36], and silicon [37][38][39], but also heavier transition metal compounds [40][41][42].…”
Section: Introductionmentioning
confidence: 99%